Characterization of mixed pellets made from rubberwood (Hevea brasiliensis) and refuse-derived fuel (RDF) waste as pellet fuel - Laosena, Rattikal; Palamanit, Arkom; Luengchavanon, Montri; Kittijaruwattana, Jitralada; Nakason, Charoen; Lee, Seng Hua; Chotikhun, Aujchariya (MDPI, 2022)
The objective of this study was to investigate the production and properties of mixed pellets made from rubberwood (Hevea brasiliensis Muell. Arg) and refuse-derived fuel (RDF) waste with no added binder. Three different conditions of mixed pellets were developed to compare their chemical and physical properties to rubberwood pellets. The produced samples were subjected to both ultimate and proximate analyses. The contents of C, H, N, S, and Cl significantly increased with the increasing amount of refuse-derived fuel in the samples, resulting in reduction of the volatile matter. The mechanical durability of the pellet samples ranged between an average value of 98 and 99%. Mixed pellets containing 50% of rubberwood and 50% of refuse-derived fuel have improved heating values by 22.21% compared to rubberwood pellets. Moreover, mixed pellets having 50% of wood and 50% of refuse-derived fuel had the highest density and the highest energy compared to the other samples. Based on the findings of this study, it appears that the manufactured mixed pellets have the potential to be used as high-energy fuel.